Why Do Bank-Dependent Firms Bear Interest-Rate Risk? - Kirti, Divya (IMF Working Papers; Working Paper ;, 2017)
I document that floating-rate loans from banks (particularly important for bank-dependent firms) drive most variation in firms' exposure to interest rates. I argue that banks lend to firms at floating rates because they themselves have floating-rate liabilities, supporting this with three key findings. Banks with more floating-rate liabilities, first, make more floating-rate loans, second, hold more floating-rate securities, and third, quote lower prices for floating-rate loans. My results establish an important link between intermediaries' funding structure and the types of contracts used by non-financial firms. They also highlight a role for banks in the balance-sheet channel of monetary policy.